Official and unofficial Latin words in 11th- and 12th-century England - Sharpe, R (Oxford University Press, 2017)
Earl and thegn, shire and sheriff, are English terms of considerable importance for the governance of England in the 11th century. I say ‘terms’ advisedly to reflect the precise sense of what they denote, because, although all three words carry a range of possible meanings, they are also part of what we must call official terminology. Putting such terms into Latin demands the creation of equivalent terms out of the Latin word-hoard, and it is well established that the Latin terminology of Anglo-Saxon England before the Norman Conquest was different from the Latin terminology adopted in England after the Conquest. The intentional replacement of pre-Conquest terminology with words current in the Latin of Normandy was driven more by the susceptibility of the older usage to misunderstanding than by any partiality to what was more familiar. What is less well understood is what any deviations from accepted terminology in Latin may represent both before and after the Conquest. This chapter will highlight a range of words intentionally used as substitutes for official terminology. It is straightforward for a dictionary to observe official usage by marking it as a definable sense, but it is more difficult to deal with words whose meaning has been temporarily appropriated because the writer chose not to use the official word. This comes down to recognising that one word has been used in place of another and therefore understanding, behind the substitute word, the sense of the word not used. The observation that different writers may substitute different words for the same term introduces a level of complexity that challenges orderly lexicography. Yet lack of guidance on such points has left editors insecure and translators floundering.